2006
DOI: 10.1002/sia.2204
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS analysis of organic impurities in UPW

Abstract: We have investigated adsorption of organic impurities in ultrapure water (UPW) on hydrophilic silicon wafer surface. The primary and tertiary amine molecules used as model compounds of organic impurities were adsorbed on the clean wafer surface during soaking in UPW. It was found that adsorbed quantities of relatively large tertiary amines among water-soluble amines, such as (C 3 H 7 ) 3 N and (C 4 H 9 ) 3 N, were higher at relatively short soak time (two h in this experiment) than at longer one (24 h). Time-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…While adsorbed quantities on hydrophobic surface decreased except for tripropylamine, those on hydrophilic surface increased as the increase of the soaking time. The adsorption behaviors on the hydrophilic surface have been investigated in the previous paper [9] and we indicated that there seems to be a good relationship between the octanol-water partition coefficients and peak intensity ratios of 24 h soaked to 2 h soaked. It was considered that the amines with large octanol-water partition coefficient are likely to be adsorbed physically on wafer surface at short soaking time because being not stable in water and replaced with the amines which have small octanol-water partition coefficients and high adsorption energy on hydrophilic wafer surface in long soaking time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While adsorbed quantities on hydrophobic surface decreased except for tripropylamine, those on hydrophilic surface increased as the increase of the soaking time. The adsorption behaviors on the hydrophilic surface have been investigated in the previous paper [9] and we indicated that there seems to be a good relationship between the octanol-water partition coefficients and peak intensity ratios of 24 h soaked to 2 h soaked. It was considered that the amines with large octanol-water partition coefficient are likely to be adsorbed physically on wafer surface at short soaking time because being not stable in water and replaced with the amines which have small octanol-water partition coefficients and high adsorption energy on hydrophilic wafer surface in long soaking time.…”
Section: Resultsmentioning
confidence: 99%
“…• C in the He atmosphere in order to remove organic contamination [9]. the same atmosphere, the wafer was cut into 10 mm×10 mm small pieces in the clean bench.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cluster-ion or polyatomic analysis beam has been used in the imaging of bio tissues [8]. In the recent years, there has been explosive growth in the quantitative analysis of organic contaminants in the semiconductor process [9,10]. It is considered that SIMS has been wide spreading the powerful mass spectrometric and imaging technique into the various fields, such as semiconductor, organic, polymer, and bio, nevertheless, the portion of contributions in the semiconductor process development has partially been declined [11].…”
Section: Introductionmentioning
confidence: 99%